Answer: The inverse of the statement f ⇒ g is ~g ⇒ ~f.
Step-by-step explanation: We are given to find the inverse of the following statement :
f ⇒ g.
Here, in the given statement, the hypothesis is p and conclusion is q.
We know that
to find the inverse of a conditional statement, we need to negate the hypothesis and conclusion and then change their position.
Therefore, the inverse of f ⇒ g will be
not g ⇒ not f
That is, ~g ⇒ ~f.
For example, the inverse of a statement "If it rains, I will go to the roof" is given by
"If I will not go the roof, then it will not rain."
Thus, the inverse of the statement f ⇒ g is ~g ⇒ ~f.